Community Service in Study Potential Technology of Education Tour and Business Prospects of Traders in Tulungagung - Sri Wahyuni Mega Hastuti; Wawan Setyawan (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2021)
The purpose of this study is to identify the potential for educational tourism, training facility and business prospects that can be developed by street vendors in Tulungagung Regency, analyze the obstacles faced by each street vendor area, determine the potential for educational tourism and business prospects for street vendors in each area in Tulungagung district. The research location is in 5 street vendors in Tulungagung district. This type of research is descriptive, namely in-depth analysis of the data that has been collected. The results showed that the street vendors’s Redjoagung Business Area have the potential to be developed and have prospects because they are strategically located on the side of the provincial road in the Stadium area and the Sports Building so that it is possible to become a Rest Area. PKL Pujasera Ngemplak has potential and prospects for development because it is close to traditional markets, fruit markets and chicken markets, so that day and night there are many buyers and training facilities. PKL Kali Ngrowo Water Front area has the potential to be developed and has prospects because it is in a river tourism area which is currently the focus of educational tourism development by the local government of Tulungagung district. The street vendors’s Pasar Senggol area have the potential to be developed and have prospects because they have a unique culinary center for food in the past, strategically located, becoming the destination for visitors who exercise in the morning. The street vendors’s Popoh Beach area have the potential to be developed and have prospects along with the improvement of Popoh Beach tourism facilities, moreover, the government's attention is quite big on the development of tourist areas and currently the Southern Cross Route is being built.